Health and safety communication: a guide for Brazilian graduate programs - Moura, Italo Emmanoel Mesquita Oliveira de (Brazilian Journal of Production Engineering, 2026)
Context: Although stricto sensu graduate students are primarily responsible for Brazilian scientific production, the lack of formal employment ties governed by the CLT (Consolidation of Labor Laws) means that this stakeholder group is not covered by the occupational health and safety management systems of public higher education institutions. Objective: This study aimed to develop an occupational safety communication guide tailored to this audience, seeking to foster a preventive culture. Method: From qualitative, descriptive, and propositive nature, the study was structured in three phases: a documentary survey of current legislation and the development of didactic material. Results: The proposed guide consists of five stages covering the contextualization of the theme, risk identification and characterization, individual and collective protection measures, emergency and first aid procedures, and the consolidation of a safety culture. For each topic, the guide specifies what should be addressed, the reference documents, and the implementation dynamics. Conclusion: The proposed guide fills an informational gap that can contribute to the physical integrity of researchers and to align university practices with the Sustainable Development Goals (SDGs).